A reading of Deuteronomy as a model of continuity, adaptation and innovation for contemporary discussions of Anglican liturgy - Corcoran, Jennifer Miriam (2017)
This work examines the important question of why there is deadlock in current Anglican discussions of fresh expressions of church. The study outlines the different perspectives represented by Mission-shaped Church and For the Parish, and how the discussions up to this point, in focusing on ecclesiology as a methodological approach, have not provided a way of bringing people together.